2012
DOI: 10.1037/a0029967
|View full text |Cite
|
Sign up to set email alerts
|

Criminal justice involvement, trauma, and negative affect in Iraq and Afghanistan war era veterans.

Abstract: Although criminal behavior in veterans has been cited as a growing problem, little is known about why some veterans are at increased risk for arrest. Theories of criminal behavior postulate that people who have been exposed to stressful environments or traumatic events and who report negative affect such as anger and irritability are at increased risk of antisocial conduct. We thus hypothesized that veterans with posttraumatic stress disorder (PTSD) or traumatic brain injury (TBI) who report anger/irritability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
107
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 32 publications
6
107
2
Order By: Relevance
“…While both SUDs and PTSD have been related to incarceration (e.g., Calhoun et al, 2005;Erickson et al, 2008;Elbogen et al, 2012), SUDs appear to be the psychiatric conditions that present the greatest risk for incarceration among both non-Iraq/Afghanistan-era (Erickson et al, 2008) and Iraq/Afghanistan-era veterans (Elbogen et al, 2012). Thus, we expected that the externalizing-SUD factor would be the psychopathology factor most strongly associated with incarceration.…”
Section: Incarceration Violence Suicide Attempts and Suicidality Amentioning
confidence: 96%
See 1 more Smart Citation
“…While both SUDs and PTSD have been related to incarceration (e.g., Calhoun et al, 2005;Erickson et al, 2008;Elbogen et al, 2012), SUDs appear to be the psychiatric conditions that present the greatest risk for incarceration among both non-Iraq/Afghanistan-era (Erickson et al, 2008) and Iraq/Afghanistan-era veterans (Elbogen et al, 2012). Thus, we expected that the externalizing-SUD factor would be the psychopathology factor most strongly associated with incarceration.…”
Section: Incarceration Violence Suicide Attempts and Suicidality Amentioning
confidence: 96%
“…There is growing recognition that criminal behavior and incarceration are significant problems among returning Iraq/Afghanistan Veterans (e.g., Elbogen et al, 2012). While both SUDs and PTSD have been related to incarceration (e.g., Calhoun et al, 2005;Erickson et al, 2008;Elbogen et al, 2012), SUDs appear to be the psychiatric conditions that present the greatest risk for incarceration among both non-Iraq/Afghanistan-era (Erickson et al, 2008) and Iraq/Afghanistan-era veterans (Elbogen et al, 2012).…”
Section: Incarceration Violence Suicide Attempts and Suicidality Amentioning
confidence: 99%
“…Regretfully, however, evidence indicates that a substantial proportion of military personnel are also involved in high-risk and antisocial behaviors that place them at jeopardy for criminal justice system involvement [2][3][4]. Indeed, recent estimates indicate that veterans comprise approximately 10% of the nation's total inmate population [5], and that veterans from the Vietnam era are substantially more likely to be involved in the criminal justice system as compared to their civilian counterparts [6]. This is not difficult to imagine as many military members are likely to be facing significant mental health concerns including, anxiety, depression, and PTSD exacerbated by the stress of military life that most civilians do not encounter [6][7][8][9].…”
mentioning
confidence: 99%
“…Recent studies indicate aggression toward others is a significant problem reported by up to one-third of OIF/OEF war veterans (Elbogen et al, 2012). The study also determined that other factors not related to military service, including growing up in a violent home life and a prior history of substance abuse also raised the risk that veterans will commit crimes (Elbogen et al, 2012). The majority of participants in the fatherhood study were non-combat veterans.…”
mentioning
confidence: 92%
“…The current demands of military service may negatively increase the risk of substance use disorders (Elbogen et al, 2012). Multiple tours of duty, improvements in body armor and medical advances may result in additional exposure to Post-Traumatic Stress Disorder (PTSD) and other trauma (e.g.…”
mentioning
confidence: 99%